Molecular markers based on 18s ribosome gene fragments of sponges (Porifera: Demospongiae) collected from Con Co island, Quang Tri province - Linh, Tran My; Mai, Nguyen Chi; Trung, Le Quang; Giang, Vu Huong; Lien, Le Quynh; Long, Le Thanh; Tuan, Phan Minh; Van, Nguyen Tuong; Ban, Ninh Khac (Academia Journal of Biology, 2014)
Sponge diversity in Vietnam has not been evaluated at all levels from phylogenetics, species, and populations to ecosystems. In the present study, the polymorphism of 18S rDNA fragment sequences revealed phylogenetic variation of 6 demosponge samples (Biemna variantia, Niphates sp., Erylus sp., Mycale laevis, Dictyonella pelligera and Hyrtios erectus) collected from Con Co island, Quang Tri province, Vietnam. High homology of DNA sequence between each studied samples and referred species in Genbank inferred six samples to be six different taxa as previously identified based on morphological characteristics, providing a potential utility of the DNA sequence for identification of sponges in Vietnam. So far, this study is the first molecular data of sponges collected from Vietnam seas. The obtained results also contribute to our better understanding of the sponge diversity in Con Co island.